A Critical Stylistic Analysis of the Ideological Positioning in Rudyard Kipling’s poem, "If" - Saad, Amira Hasan Ahmed; Sarbini, Mona Lisa (Technium Social Sciences Journal, 2021)
This paper deals with the ideological positioning of the English poet, Rudyard Kipling in a selected poem, entitled "If", as regards to the theme of the heroic attributes of –Wisdom, Strength, and Courtesy. The researcher adopts a branch of stylistics, called Critical Stylistics, as proposed by Jeffries (2010) in order to uncover the ideologies of the poet regarding the topic concerned and how linguistic choices are used to display his ideas. The model is comprised of ten tools of analysis which, upon being applied to the selected poem, have shown how the poet exploits language resources in order to pass his ideology and influence his readers. In this paper, the ten tools are presented as applied to the whole poem. The objective of the study is to examine how Kipling’s poem astonishingly excels in giving advice and how it is easier to give advice than being guided by it. The model of stylistics used in this analysis also includes in it these tools that have predominantly been applied to small-scale qualitative analyses. Findings from the analysis reveal the ways in which sets of beliefs and advice may be structured in the language of wisdom and compassion, and, more specifically, the ways in which Kipling’s ideological attitudes and assumptions are embedded in the structure of his poems. Moreover, how this poem articulates the significance of burying the gap between the generations. The old should instruct and the young in turn should listen and learn from the experiences of the old. Such ideological assumptions about listening to the previous generation experiences and have the liberty to abide by or reject their ways of thinking.